Noninvasive Brain Stimulation and Implications for Nonmotor Symptoms in Parkinson's Disease - Rektorová, Irena; Anderková, Ľubomíra (International review of neurobiology, 2017)
Transcranial noninvasive brain stimulation includes both repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS). TMS uses a rapidly changing magnetic field to induce currents and action potentials in underlying brain tissue, whereas tDCS involves the application of weak electrical currents to modulate neuronal membrane potential. In this chapter, we provide a literature review with a focus on the therapeutic potential of both techniques in the treatment of nonmotor symptoms of Parkinson's disease (PD). On the whole, the results of studies are rather preliminary but promising as they show some positive effects of rTMS and tDCS particularly on depressive symptoms and cognitive dysfunctions in PD. More carefully controlled trials with standardized methodology, adequately sized and well-characterized samples, and the inclusion of multimodal approaches are warranted in the future.
Keywords: klinické zkoušky jako téma; Clinical Trials as Topic; Cognitive Dysfunction; Parkinsonova nemoc; Nonmotor; Electrophysiology; lidé; transkraniální magnetická stimulace; Transcranial Direct Current Stimulation; mozek; Functional MRI; Brain; Noninvasive brain stimulation; kognitivní dysfunkce; Cognition; Transcranial Magnetic Stimulation; deprese; přímá transkraniální stimulace mozku; Transcranial direct current stimulation; Depression; Repetitive transcranial magnetic stimulation; Parkinson Disease; Humans